Synthesis of anti-inflammatory α-and β-linked acetamidopyranosides as inhibitors of toll-like receptor 4 (TLR4). Issue 23 (3rd June 2015) - Wipf, Peter; Eyer, Benjamin R.; Yamaguchi, Yukihiro; Zhang, Feng; Neal, Matthew D.; Sodhi, Chhinder P.; Good, Misty; Branca, Maria; Prindle, Thomas; Lu, Peng; Brodsky, Jeffrey L.; Hackam, David J.
Graphical abstract: Abstract: The low-molecular weight isopropyl 2-acetamido-α-glucoside 16 (C34) inhibits toll-like receptor 4 (TLR4) in enterocytes and macrophages in vitro, and reduces systemic inflammation in mouse models of endotoxemia and necrotizing enterocolitis. We used a copper(II)-mediated solvolysis of anomeric oxazolines and an acid-mediated conversion of β-glucosamine and β-galactosamine pentaacetates to generate analogs of 16 at the anomeric carbon and at C-4 of the pyranose ring. These compounds were evaluated for their influence on TLR4-mediated inflammatory signaling in cultured enterocytes and monocytes. Their efficacy was confirmed using a NF-kB-luciferase reporter mouse, thus establishing the first structure–activity relationship (SAR) study in this series and identifying the more efficacious isopropyl 2-acetamido-α-galactoside 17 .